Monetary Coordination and Regulation Policies of Spillover Effects on Asset Dynamics - Kılıç, Erdem (Springer, 2017)
In this study we propose a model for excessive volatility regulation. The model dealswith the control of shocks in capital markets. After describing a transmission mechanism thattransfers shocks in a macroeconomic variable, we establish a model how to control the shocks inthe framework. Two economies are considered with alternative constellations in coordination ofpolicies. Spillover effects under coordination are less severe, than the spillover effects under Nashequilibrium in the case of comovements of asset volatilities. In other terms, coordination helps tocure the contagious effects, in the case, where two countries are affected by the same spillovereffect in the same direction.
Keywords: Asset dynamics; Spillover effects; Monetary coordination; Regulation policies